Providing help to multicultural patients in the context of contemporary population migrations in Europe - Kiszka, Jerzy; Ozga, Dorota; Mach, Arkadiusz; Krajewski, Romuald (Nursing in the 21st Century, 2018)
PROVIDING HELP TO MULTICULTURAL PATIENTS IN THE CONTEXT OF CONTEMPORARY POPULATION MIGRATIONS IN EUROPEIntroduction. The population migration to the countries of the European Union (EU) of the conflict of war has grown substantially in recent years. According to the Office for Foreigners in Poland are staying 586 thousand foreigners. 279 refugees from Syria arrived in Poland in 2015. The economic development of Poland means that the number of foreigners settling in or crossing Poland and using the services of the Polish health service is constantly growing. Foreigners from outside Europe (the largest groups are Vietnamese – 8.8 thousand and Chinese – 6.2 thousand) were brought up in a different culture, but also people from European countries (the largest group are immigrants from Ukraine – 513 thousand) may differ from Poles perceive health and illness. Health Personnel may encounter difficulties in providing medical assistance and taking care of a culturally different patient. They may result from the language barrier, lack of knowledge about the differences in patients’ expectations or lack of skills in communication with the patient. The result may be improper assistance, violation of patients’ rights and avoiding the use of medical services.Aim. Presentation of the migration of population in EU countries, analysis of problems arising during the provision of assistance to culturally different patients and an indication of the possibility of developing cultural competences of paramedics, nurses and doctors through education in this area.